2015
DOI: 10.1371/journal.ppat.1004979
|View full text |Cite
|
Sign up to set email alerts
|

EBV BART MicroRNAs Target Multiple Pro-apoptotic Cellular Genes to Promote Epithelial Cell Survival

Abstract: Epstein-Barr virus (EBV) is a ubiquitous human γ-herpesvirus that can give rise to cancers of both B-cell and epithelial cell origin. In EBV-induced cancers of epithelial origin, including nasopharyngeal carcinomas (NPCs) and gastric carcinomas, the latent EBV genome expresses very high levels of a cluster of 22 viral pre-miRNAs, called the miR-BARTs, and these have previously been shown to confer a degree of resistance to pro-apoptotic drugs. Here, we present an analysis of the ability of individual miR-BART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 46 publications
(129 reference statements)
3
86
1
1
Order By: Relevance
“…In the time since the publication of our high-throughput experiment that proposed CASP3 as a target of EBV miRNAs, several groups have published conflicting evidence of this interaction [11, 18, 22, 24, 25]. Here we confirmed that human CASP3 is a direct target of nine EBV BART miRNAs in luciferase assays by testing all canonical, predicted sites.…”
Section: Discussionsupporting
confidence: 75%
“…In the time since the publication of our high-throughput experiment that proposed CASP3 as a target of EBV miRNAs, several groups have published conflicting evidence of this interaction [11, 18, 22, 24, 25]. Here we confirmed that human CASP3 is a direct target of nine EBV BART miRNAs in luciferase assays by testing all canonical, predicted sites.…”
Section: Discussionsupporting
confidence: 75%
“…AGS cells infected with EBV express high levels of the BART miRNAs (15), and previous profiling of one AGS line by microarray suggested that a substantial subset of the downregulated genes after latent infection were direct targets of the BART miRNAs (4). To confirm that the BART miRNAs contribute to the changes in gene expression profiled in the multiple infected cell lines in this report, the genes changed in expression were overlapped with the most extensive lists of BART miRNA targets published to date, where the BART miRNA targets were identified by PAR-CLIP in a peripheral effusion lymphoma cell line dually infected with EBV and KSHV, as well as the NPC cell line C666 (25,26). A higher percentage of the downregulated genes and a lower number of the upregulated genes overlapped with the PAR-CLIP data sets compared to the null hypothesis, which would be the percentage of all genes expressed in AGS cells (based on the RNA-seq data) that overlap the PAR-CLIP data set ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…So far, EBV-encoded miRNAs have been shown to play a role in immune evasion (Albanese et al, 2016; Tagawa et al, 2016; Xia et al, 2008), apoptosis (Kang et al, 2015; Lei et al, 2013), and inhibition of tumor suppressors (Bernhardt et al, 2016). Additionally, inactivation of the miR-BHRF1 miRNA cluster results in a reproducible and robust reduction in B cell transformation and LCL growth (Feederle et al, 2011a, 2011b; Haar et al, 2015; Seto et al, 2010), which suggested that the miR-BHRF1 miRNA cluster was promoting EBV transformation by downregulating the expression in trans of cellular mRNAs that inhibit this process.…”
Section: Introductionmentioning
confidence: 99%